Precision Aging: Applying Precision Medicine to the Field of Cognitive Aging - Ryan, Lee; Hay, Meredith; Huentelman, Matt J.; Duarte, Audrey; Rundek, Tatjana; Levin, Bonnie; Soldan, Anja; Pettigrew, Corinne; Mehl, Matthias R.; Barnes, Carol A. (Frontiers in Aging Neuroscience, 2019)
The current ‘one size fits all’ approach to our cognitive aging population is not adequate to close the gap between cognitive health span and lifespan. In this review paper, we present a a novel model for understanding, preventing, and treating age-related cognitive impairment (ARCI) based on the concepts precision medicine. We will discuss how multiple risk factors can be classified into risk categories because of their interrelatedness in real life, the brain drivers or common mechanisms mediating brain aging, and the genetic variants that increase sensitivity to, or ameliorate, risk for ARCI. Rather than providing a definitive model of risk for ARCI and cognitive decline, the Precision Aging model is meant as a starting point to guide future research. To that end, after briefly discussing key risk categories, brain drivers, and genetic risks, we conclude with a discussion of steps that can be taken to move the field forward.